Generalized Rough Γ-Hyperideals in Γ-Semihypergroups - Naveed Yaqoob (Journal of Applied Mathematics, 2014)
Davvaz (2008) introduced the concept of set-valued homomorphism and T-rough sets in a group. In this paper, we consider the set-valued homomorphism T on Γ-semihypergroup H to interpret the lower and upper approximations. We study the roughness of (m,n) bi-Γ-hyperideals and (m,n) quasi-Γ-hyperideals in terms of set-valued homomorphisms, which are extended notions of (m,n) bi-Γ-hyperideals and (m,n) quasi-Γ-hyperideals of Γ-semihypergroups.